(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
The article explores the main ideas and character portrayals in Mukhtar Auezov’s drama “Enlik – Kebek.” It focuses on how the author reflects the eternal theme of love through the tragic fate of Enlik and Kebek, revealing the struggle between human freedom and traditional customs. In addition, the educational and aesthetic significance of teaching dramatic works is highlighted, emphasizing their role in developing students’ creative abilities.